The difficult crossroads of decisions at COVID-19: how can the deontology implicit in Evidence-Based Medicine help us to understand the different attitudes of doctors at this time? - NACUL,MIGUEL PRESTES (2020)
ABSTRACT One of the struggles faced by physicians in clinical decisions during the COVID-19 pandemic is how to deal with already available or lacking scientific evidence. The COVID-19 pandemic has a large impact in the routine of the many health services, including surgery, which demanded changes in assist protocols. Questions began to arise about well-established surgery conducts due to situations related to SARS-COV-2 infection, and, according to public health measures that are necessary to fight the pandemic. In situations of scarce available evidence, it is natural for us to have to deal with systematically more fragile, provisory and bias-susceptible information. Considering the principles that guide Evidence Based Medicine and Bioethical, the authors analyze the complexity of the medical decision-making during this time. Medical conducts must be adapted to the context of fighting the pandemic and consider patients and healthcare providers exposure and well-being and, lastly, the conservation of resources. The authors conclude that acceptance and tolerance to divergence is commendable, being a path to achieving unity in the diversity of medicine in times of little safe knowledge.